COMPARATIVE ANALYSIS OF WATER QUALITY FROM PRIVATE SOURCES AND WATER SUPPLY OF KHARKIV - Кравченко, Н. Б.; Зеленська, Е. І. (Man and Environment. Issues of Neoecology)
Private drinking water sources of the Lenin and Dzerzhinsky district in Kharkov – «Sarzhin yar» and the park «Unist» were investigated and for comparison - tap water. Complex rating evaluation of drinking water sources in Kharkov was calculated on socio-economic indicators by which determined that the best in terms of customer is the source of «Sarzhyn yar» and for pH value meets STATE STANDARDS 2.2.4-171-10. The concentrations of trace elements in water from all sources studied are in the normal range.